Strategi Pengembangan Merek Pada Sawah Lope di Desa Cikaso Kuningan - Donant Alananto Iskandar; Joseph MJ Renwarin; Anandra Isjiwo; Anna Maria Godeliva; F.X. Jordi Hanzdima; Ifdlal Muhammad Amir; Jordy Alvoyage; Muhammad Rio Adipratama; Rut Miranda Lumbantobing; Septyano Fabian Prasetyo (LPMP Imperium, 2023)
Kuningan is one of the areas in Indonesia with a lot of tourism potential. Even though there are many tourist destinations in Kuningan, local and foreign tourists rarely know about tourist attractions, especially tourist villages in Kuningan. Sawah Lope is one of them, Sawa, located in the village of Cikaso Kuningan, has many beautiful tourist attractions and natural resources that tourists rarely visit. This situation can happen because the residents there and the local government cannot carry out promotions and market their area so that they can be attracted by tourists, from local to foreign tourists. Sawah Lope is a Nature Tourism that utilizes views of rice fields and irrigation as tourist objects to attract the attention of visitors and the surrounding community. This lope rice field tourism is managed by two community organizations: Tourism Awareness Group and Village Owned Enterprises (Bumdes). Thus, the cooperation of these two community organizations has an essential influence on the continuity and progress of tourism objects.